Laser stabilization of GMAW additive manufacturing of Ti-6Al-4V components - Pardal, Goncalo; Martina, Filomeno; Williams, Stewart W. (Elsevier, 2019)
GMAW (Gas Metal Arc Welding) of titanium is not currently used in industry due to the high levels of spatter generation, the wandering of the welding arc and the consequent waviness of the weld bead. This paper reports on the use of laser welding in conduction mode to stabilize the CMT (Cold Metal Transfer), a low heat input GMAW process. The stabilization and reshaping of Ti-6Al-4 V weld beads was verified for laser hybrid GMAW bead on plate deposition. The laser beam was defocused, used in conduction mode, and was positioned concentric with the welding wire and the welding arc (CMT). Finally, the results obtained for bead-on-plate welding were applied to an additively manufactured structure, in which a laser-hybrid stabilized sample was built and then evaluated against CMT-only sample. This work reveals that laser can be used to stabilize the welding process, improve the weld-bead shape of single and multiple layer depositions and increase the deposition rate of additive manufacture of Ti-6Al-4 V from1.7 kg/h to 2.0 kg/h.
Keywords: Laser welding; GMAW; Stabilization; Additive manufacturing; Ti-6Al-4V